Pengunaan Media Ban Terhadap Peningkatan Kemampuan Pointing Pada Atlet Petanque Kabupaten Kuburaya - Anjeli; Fallo, Ilham Surya; Sabransyah, Mohammad (Journal Sport Academy, 2023)
Based on the results of observations made during the PORPROV 2022 event, the researchers found a problem, namely when competing in the Kuburaya Regency petanque athletes made many mistakes when throwing pointing at long distances, namely where the distance of 8-9 meters the point where the shot fell was not right, causing many points to fail and benefited the opposing team a lot as a result of failed points. Therefore, the researcher was interested in taking the title "The Effect of Training Using Tire Media on Increasing Pointing Ability in Squatting at a Distance of 9 Meters in Petanque Athletes in Kuburaya Regency" the purpose of this study was to see an increase in Pointing Ability in Squatting 9 Meters. This type of research is experimental research that is used to see and determine the effect of cause and effect between the independent and dependent variables. Data analysis technique is calculated by test (t). Data g test results T count = 7.146 and T table = 2.228 there is an increase of 4.918. The pretest data = 11.5 and the posttest data = 18.9. The results of the hypothesis test show that R count = 0.930, the value of R table = 0.631 both data R count and R table have a significant effect. The conclusion using the training method using the media tire on increasing the ability to point in squats at a distance of 9 meters.